2021
DOI: 10.1177/10497323211049225
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Health Work of Women With Female Genital Cutting Prior to Reproductive Health Care Encounters

Abstract: We used institutional ethnography to explore the social relations that shaped the reproductive health care experiences of women with female genital cutting. Interviews with eight women revealed that they engaged in discourse that opposed the practices of cutting female genitals as a human-rights violation. This discourse worked to protect those affected by the practices, but also stigmatized female genital cutting, making participants anticipate experiencing stigmatization during health care. Women’s engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Perhaps in part due to discrimination based on their migrant status and religion, Somali individuals (especially in FGM/Caffected communities) have reported feeling "not normal" and "different" in their Western host country [68] a notion perpetuated by discriminatory public discourse depicting the "barbaric" nature of FGM/C and related cultures [69]. A critical discourse analysis of Somali men and women found that Somalis described experiencing discrimination regarding their Muslim identities and that these experiences had perceived impacts on their use of health services [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps in part due to discrimination based on their migrant status and religion, Somali individuals (especially in FGM/Caffected communities) have reported feeling "not normal" and "different" in their Western host country [68] a notion perpetuated by discriminatory public discourse depicting the "barbaric" nature of FGM/C and related cultures [69]. A critical discourse analysis of Somali men and women found that Somalis described experiencing discrimination regarding their Muslim identities and that these experiences had perceived impacts on their use of health services [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider the ways in which distress related to vivid recollection of the original FGM/C experience can be triggered when women traverse social systems such as health care [34]. For example, women with FGM/C in Canada have reported such recollection elicited by vulvar/vaginal examinations, in which their doctors did not know how to care for their resultant emotional responses [69]. Similarly, West African women with FGM/C reported negative and insensitive reactions from medical professionals regarding their FGM/C status that created feelings of shame [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we found that the goal of eradicating FGC on a global level was entangled in anti-female genital mutilation (FGM) public conversations. Although those who engaged in/co-produced anti-FGM discourse (such as media and news outlets) often aimed to “protect” uncut girls and women and advocate for women with FGC, these discursive strategies also often resulted in the stigmatization of women, their bodies, and their cultures (Jacobson et al, 2021 ). This is not the first instance in which the “stigmatizing nature of much current activist, academic, and social-policy discourse” regarding FGC has been discussed (for example, see Earp, 2020a , p. 1).…”
Section: Introductionmentioning
confidence: 99%